The Reconstruction of Ratok Bawak to Ratok Laher Pangulu Drama: Sentimental Study - Nurwani (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
This study aims to look at the sentimental values ​​contained in the drama of Ratok Lareh Pangulu dance drama. Rokok Lareh Pangulu is an embodiment of ratok bawak. As a form of reconstructive Ratok Bawak, the substance, character, contents, points and essence of Ratok Lareh Pangulu dance drama are closely related to the sentimental feelings of the wives and the community when they lose Pengulu, as is the case with Ratok Bawak. Sentimentil are things that are involves feelings, feeling subtle, and easily moved. In order to know the sentimental sense in Ratok Lareh Pangulu as a form of transformation of Ratok Bawak, sentimental theory is used according to Cliford Geertz. The research method was conducted using qualitative methods including literature review, observation, interviews, and documentation. Documentation is done by reconstructing the lamenting culture. The creation of works begins with pondering and interpreting, reinterpreting, exploring, improvising and forming. In Ratok Lareh Pangulu drama, there is a sentimental sense born of emotions built from individuals placed together in Ratok Lareh Pangulu. Fear of the risk felt by the mother and wife of Penghulu has to do with mental, scientific, occupational, and material matters. Desperation because losing the closest person is something sad and frightening. Sentimentality also relates to the enjoyment of victory.